Perwujudan Asas Keadilan dan Keseimbangan dalam Pembuatan Akta Persekutuan Komanditer Berdasarkan Akad Mudharabah - Ardiansyah, Momon; Hamidah, Siti; Mochtar, Dewi Astuti (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This study discusses the creation and realization of the principle of justice and the balance of limited partnership deed (commanditaire vennootschap) based on mudharabah contracts. The method uses normative legal research to analyze the principle of justice in contracts based on mudharabah contracts on the formation of limited partnership through literature review and exploring positive laws that apply. The results show the principle of justice and balance in forming a limited partnership using the mudharabah contract is reflected if one form of cooperation is based on a sense of help and its implementation fulfills the principle of fairness both in determining profits, losses, and relating to the termination of the cooperation agreement.